Taming the Puritan: Bibliometric Mapping and Critical Review of the Global Salafism Discourse Trajectory - Lutfi, Muhammad; Ahmad Nur Fuad (Journal of Islamic Philosophy and Contemporary Thought, 2025)
This study maps the trajectory of academic discourse on global Salafism (2000–2025) using a mixed-methods approach integrating bibliometric analysis and critical review. Quantitative findings reveal a radical "epistemic decentralization" and structural shift. Geographically, the Global North’s hegemony is eroding; Indonesia (46 papers) has emerged as the closest competitor to the US (50), with UIN Sunan Kalijaga ranking as the world’s most productive institution (8 papers), surpassing elite Western universities. Bibliometric mapping further reveals a shift in knowledge structure: the discourse has transitioned from dense “terrorism” and “security” clusters toward “social movement,” “gender,” and “digital identity” nodes. Authorial authority is polycentric, led jointly by scholars like Cavatorta, Duderija, Pall, and Wagemakers, without a single dominant figure. Qualitatively, the discourse evolved in three phases: (1) The Security Phase (2000–2010), dominated by perspectives viewing Salafism solely as a source of terror post-9/11; (2) The Fragmentation Phase (2010–2020), driven by the Arab Spring, highlighting internal divisions and digital activism; and (3) The "Post-Salafism" Era (2021–2025), where the movement is domesticated by state nationalism and algorithmic discipline. The study concludes that Salafism is no longer a monolithic threat but a hybrid entity, requiring a digital sociological approach to understand its new adaptations.